Guilt-Tripping the Greengrocer. Issue 2 (May 2018) - Lukes, Steven Michael
Two ways of reading Havel's classic essay are proposed. According to the first, the focus is on the peculiarities of the post-totalitarian system, inhabited by the famous greengrocer, where slogans, ritual communication, pervasive manipulation, and arbitrariness prevail and power operates as if automatic and anonymous. The lines of conflict run though each person: everyone is both victim and supporter. Comparison is made with Michel Foucault's (early) view of power, which similarly rejected seeing power as exercised by some over others, stressing power's anonymity and pervasiveness. For Foucault, at that stage of his thinking, however, power constitutes "regimes of truth, " whereas for Havel the "power of truth" is a force that has the potential successfully to resist and subvert domination. The power of truth is that of the greengrocer and others "living within the lie" to expose and shatter the world of appearances. Havel calls on them to end their complicity. This might seem moralistic, but Havel's view was that under post-totalitarian conditions, morality would prove the best strategy. The second reading suggests that the post-totalitarian system is the "extreme version of technological civilization and the industrial-consumer society." But this account of power is at odds with the first, since in this view the powerless would have no prospects of resisting and overcoming domination. Havel's account is thus political and relevant to other political contexts, raising several empirical questions concerning the dynamics of power and the conditions for the success of morally fueled protest and normative questions concerning power and responsibility.